Pengaruh Kurikulum, Motivasi Dan Kemampuan Penulisan Karya Ilmiah Terhadap Penyelesaian Tugas Akhir (TA) Mahasiswa Prodi DIII Teknik Komputer Politeknik Harapan Bersama - Adi Candra Kusuma; Ida Afriliana; Eko Budihartono (Cakrawala: Jurnal Pendidikan, 2018)
The demands in the Final Project for Diploma students are to carry out the research process correctly in accordance with the applicable rules without having to find and correct theories that have less readiness for students to face the final project, 2) the low motivation of students to complete on time, 3) lack of substance of information (seminars, workshops) related to hardware for students who take the hardware theme, 4) student learning reference sources are only fixated on the lecturers, 5) student environment that does not support to finish the final project such as the influence of friends, lack of family encouragement, and finance. This study aims to determine the influence of curriculum, motivation and the ability to write scientific papers on the completion of the final project (TA) of DIII Computer Engineering students. This research is quantitative research by testing the normality test, correlation test, simple linear regression test and multiple linear regression test. With the results of the study showed the influence of the relationship of motivation (X1), study program curriculum (X2), the ability to write scientific papers (X3) together on the completion of the student's final assignment (Y) of 88.5%. Partially, the influence of motivation factor (X1) is 48.1%, study program curriculum (X2) is 75.7%, and the ability to write scientific work (X3) is 40.9%. The regression equation is Y = -1.344 + 0.854 X_1 + 1.400 X_2 + 0.722 X_3.